2012
DOI: 10.1002/elan.201100555
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalysis of Trace Inorganic Arsenic with Gold Nanoelectrode Ensembles

Abstract: The results of a study on the determination of trace levels of arsenic with nanoelectrode ensembles (NEEs) are reported. In order to lower the detection limit and to increase the number of performable analysis for each NEE, the right choice of the supporting electrolyte concentration and electroanalytical parameters were optimized. The electrochemical behavior of As(III) at NEEs was studied at first by cyclic voltammetry, while trace concentrations of As(III) were determined by anodic stripping square wave vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 42 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…The largest part of these studies was developed using ensembles of gold nanoelectrodes (NEEs) prepared via electroless deposition. From an analytical viewpoint, metals different from Au were seldom studied, with few exceptions such as for instance, Bi modified NEEs [8], applied for ultratrace lead (II) analyses. Recently, a simple and effective electrodeposition method for obtaining copper NEEs was proposed [9], where copper is an interesting electrode material suitable for the detection of analytes electroactive at negative potential values.…”
Section: Introductionmentioning
confidence: 99%
“…The largest part of these studies was developed using ensembles of gold nanoelectrodes (NEEs) prepared via electroless deposition. From an analytical viewpoint, metals different from Au were seldom studied, with few exceptions such as for instance, Bi modified NEEs [8], applied for ultratrace lead (II) analyses. Recently, a simple and effective electrodeposition method for obtaining copper NEEs was proposed [9], where copper is an interesting electrode material suitable for the detection of analytes electroactive at negative potential values.…”
Section: Introductionmentioning
confidence: 99%
“…compared GNEE on basal-plane graphite modified electrode with GNEE on glassy carbon and macro gold electrode and found that the former had higher sensitivity(Dai and Compton 2005) Mardegan et al, (2012). reported a detection limit of 0.005µg/L with gold nano electrode ensemble (Au-NEE)(Mardegan et al 2012) Kamenev et al, (2001). reported graphite electrodes modified with gold and copper with detection limit of 17µg/L and 47µg/L respectively(Kamenev et al 2001), whereas a better detection limit (7µg/L) was obtained with gold-graphite electrode(Kamenev et al 2005) Beinrohr (2001)(Beinrohr 2001).…”
mentioning
confidence: 97%
“…compared GNEE on basal-plane graphite modified electrode with GNEE on glassy carbon and macro gold electrode and found that the former had higher sensitivity(Dai and Compton 2005) Mardegan et al, (2012). reported a detection limit of 0.005µg/L with gold nano electrode ensemble (Au-NEE)(Mardegan et al 2012) Kamenev et al, (2001).…”
mentioning
confidence: 98%
“…For example, LODs in the range 0.01-0.05 ppb are presented in [26,[36][37][38][39][40][41][42] and LOD lower than 0.005 ppb in [43][44][45][46][47][48]. A number of different approaches have been used to improve the sensitivity of detection:…”
Section: As(iii) Determination By Anodic Stripping Voltammetry (Asv)mentioning
confidence: 99%